Fibre bridging effect on the Paris relation for mode I fatigue delamination growth in composites with consideration of interface configuration. (1st January 2017) - Yao, Liaojun; Sun, Yi; Alderliesten, R.C.; Benedictus, R.; Zhao, Meiying
Abstract: Fibre bridging can significantly enhance delamination resistance making the use of a single Paris resistance curve to determine fatigue crack growth insufficient. An empirical Paris-type relation has been developed in a previous study to take fibre bridging into account in fatigue delamination growth. This relation was developed by correlating the Paris constants C and n to the amount of fibre bridging. This paper provides a further investigation on the interface configuration effect on fatigue delamination growth, illustrating the significance of fibre bridging. The results demonstrated that more bridging fibres can be generated in a multidirectional interface, making both log( C ) and n significantly depend on fibre bridging. Thus, the method proposed in the previous study is further extended to take into account of the interface configuration effect.